2003
DOI: 10.1093/emboj/cdg180
|View full text |Cite
|
Sign up to set email alerts
|

The yeast Sgs1 helicase is differentially required for genomic and ribosomal DNA replication

Abstract: The members of the RecQ family of DNA helicases play conserved roles in the preservation of genome integrity. RecQ helicases are implicated in Bloom and Werner syndromes, which are associated with genomic instability and predisposition to cancers. The human BLM and WRN helicases are required for normal S phase progression. In contrast, Saccharomyces cerevisiae cells deleted for SGS1 grow with wild-type kinetics. To investigate the role of Sgs1p in DNA replication, we have monitored S phase progression in sgs1D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 62 publications
5
86
2
Order By: Relevance
“…Importantly, DNA combing studies also revealed the presence of large inactive regions in HU-treated cells (Tourriere et al 2005;Versini et al 2003). These domains are absent in checkpoint mutants, indicating that they correspond to latereplicating regions repressed by checkpoint kinases (Tourriere et al 2005).…”
Section: Single-molecule Analysis: Lessons From Yeastmentioning
confidence: 96%
See 1 more Smart Citation
“…Importantly, DNA combing studies also revealed the presence of large inactive regions in HU-treated cells (Tourriere et al 2005;Versini et al 2003). These domains are absent in checkpoint mutants, indicating that they correspond to latereplicating regions repressed by checkpoint kinases (Tourriere et al 2005).…”
Section: Single-molecule Analysis: Lessons From Yeastmentioning
confidence: 96%
“…In this approach, an asynchronous population of cells is pulsed-labeled for a short period of time with halogenated nucleotides to determine the position of replication origins (arrowheads). DNA fibers can be counterstained with anti-ssDNA antibodies (blue) (Versini et al 2003), and specific regions can be analyzed by FISH (Lebofsky et al 2006); c DNA combing analysis of densely spaced origins in Xenopus egg extracts (Marheineke and Hyrien 2001). Initiation sites are labeled with DIG-dUTP (red) to mark replication origins (arrowheads) after release from an aphidicolin block and biotin-dUTP (green) is added at variable times until completion of DNA replication; d DNA combing analysis of interorigin distances (IODs) in yeast.…”
Section: Single-molecule Analysis Of Dna Replication Profilesmentioning
confidence: 99%
“…In the absence of Sgs1, the stalled forks could be rescued through a recombinogenic mechanism that may proceed in a similar way to that described above. Recently, Versini et al (2003) showed that DNA replication is specifically retarded at the rDNA locus in sgs1 cells and suggested that this could be due to their inability to prevent recombination at stalled forks, abundant in that region. It remains to be seen whether these proposed mechanisms of rDNA maintenance can be extrapolated to S. pombe and other eukaryotes.…”
Section: Slx1-slx4 Endonucleasementioning
confidence: 99%
“…We used the single-molecule method of DNA combing (13)(14)(15) and genomic microarrays (16) to probe coordination of DNA replication. By using DNA combing, we found that in individual Escherichia coli chromosomes the relative progress of the two replisomes was highly variable; most of the time, the leftward replisome was farther from oriC.…”
mentioning
confidence: 99%